A new species of the genus Oiketicoides Heylaerts, 1885 (Lepidoptera, Psychidae) from Korea with its natural parasitoid enemy - Dong-June Lee; Jongwon Kim; Seung-Su Euo; Jae-Seok Lee; Hyeon Lee; Seung Jin Roh (ZooKeys)
Oiketicoides gohadoensis Roh & Lee, sp. nov. is described as new to science. The morphology of male adult, including genitalia, is described, and DNA barcodes for precise identification of the species are provided. A parasitoid, Neophryxe psychidis Townsend, 1916 (Diptera, Tachinidae) of O. gohadoensis is also reported for the first time in Korea, together with its DNA barcode sequence.